Analisis Resepsi Followers Terhadap Pesan Kesehatan Seksual Akun Instagram @catwomanizer - Alifia Rahman, Jasmine Zaffira; Putri Aisyiyah Rachma Dewi, (The Commercium, 2025)
This research aims to analyze followers' reception of sexual health messages conveyed by the Instagram account @catwomanizer. This research uses descriptive qualitative methods with Stuart Hall's reception theory approach, identifying three categories of reception, namely: dominant, negotiation, and opposition. The majority of followers are in a dominant position, receiving sexual health education messages positively and using them to increase awareness of reproductive health. Meanwhile, some followers are in a position of negotiation and opposition, rejecting or adapting the meaning of the message. Followers interpret and receive messages differently between individuals, influenced by several factors such as environment, work profession, educational background, gender, and personal experience. The research results show that social media is effective as a means of sexual health education, although challenges related to conservative social norms still exist.